Morphometric analyses as a tool for the delimitation of a species complex of rupicolous Cattleya orchids from the Brazilian campos rupestres of Minas Gerais and Bahia - Lima, André P.; Silva, João Rodrigo S.; Siqueira, Gabriela B.; Berg, Cássio Van Den (Phytotaxa, 2024)
In the present study we perform a linear morphometric analysis to assess species delimitation in Cattleya caulescens, C. pabstii, and C. pfisteri, which constitute a species complex in Brazilian campos rupestres. For this purpose, we collected 18 linear measurement variables from flowers of 153 individuals in 11 populations from the three species in the Brazilian States of Minas Gerais and Bahia. We applied Principal Component Analysis (PCA), Canonical Variate Analysis (CVA) and cluster analysis to assess the morphological variation between populations. The analyses indicated a clear difference and cohese clusters of populations for each species, but one of the populations of C. pfisteri was divergent from the other populations. This difference is putatively explained by genetic data from other studies that suggest introgression from a species from a different series, C. sincorana, in this location. The differences between C. caulescens and C. pabstii reinforce the floristic differentiation of the orchid flora from the quartzitic mountains of Southern Minas Gerais in relation to the Espinhaço range to the north, as well as the development of a specialized orchid flora in the iron ore outcrops in Central Minas Gerais.